Bringing Outsiders In : Transatlantic Perspectives on Immigrant Political Incorporation - Mollenkopf, John H., 1946-; Hochschild, Jennifer L., 1950- (Book collections on Project MUSE., 2009)
For immigrants, politics can play a significant role in determining whether and how they assimilate. In Bringing Outsiders In, leading social scientists present individual cases and work toward a comparative synthesis of how immigrants affect-and are affected by-civic life on both sides of the Atlantic. Just as in the United States, large immigrant minority communities have been emerging across Europe. While these communities usually make up less than one-tenth of national populations, they typically have a large presence in urban areas, sometimes approaching a majority. That immigrants can have an even greater political salience than their population might suggest has been demonstrated in recent years in places as diverse as Sweden and France. Attending to how local and national states encourage or discourage political participation, the authors assess the relative involvement of immigrants in a wide range of settings. Jennifer Hochschild and John Mollenkopf provide a context for the particular cases and comparisons and draw a set of analytic and empirical conclusions regarding incorporation. Contributors: Richard Alba, CUNY Graduate Center; Sandro Cattacin, University of Geneva; Gianni D'Amato, University of Neuchatel; Jan Willem Duyvendak, University of Amsterdam; Nancy Foner, Hunter College and CUNY Graduate Center; Luis Fraga, University of Washington; Jennifer Hochschild, Harvard University; Christian Joppke, American University of Paris; Gallya Lahav, SUNY Stony Brook; Marco Martiniello, University of Liege; Michael Minkenberg, New York University and European University Viadrina; Lorraine Minnite, Barnard College and Columbia University; Tariq Modood, University of Bristol; John Mollenkopf, CUNY Graduate Center; Eva Ostergaard-Nielsen, Autonomous University of Barcelona; Adrian Pantoja, Pitzer College; Trees Pels, Verwey-Jonker Institute for Social Research; Rally Rijkschroeff, Verwey-Jonker Institute for Social Research; Reuel Rogers, Northwestern University; Peter Schuck, Yale Law School and New York University Law School; Raphael Sonenshein, California State University, Fullerton; Janelle Wong, University of Southern California.